Understanding the policies of the BRICS countries in R2P cases: An English school perspective - OĞUZ GÖK, GONCA (My University, 2022)
This article’s main aim is to evaluate the position of brics ‘as a group’ towards the Responsibility to Protect (r2p) norm by locating it in the framework of the English School’s pluralist versus solidarist debate. It traces the pluralist and solidarist elements in brics discourses and decisions towards r2p by scrutinising the content of the ten brics summit declarations between 2011 and 2020 and the voting of brics members on UN Security Council resolutions regarding seven cases involving atrocity crimes (Syria, Yemen, Mali, Ivory Coast, Central African Republic, South Sudan, Libya) discussed at the UN Security Council. The article argues that although there is an obvious quantitative increase in brics common pluralist agenda, they do not demonstrate group solidarity in practice and have not yet socialised to act as a group on the r2p as a key norm of global governance. Therefore, their position as a group towards r2p could best be framed as ‘Charter solidarism’ in principle per se, not in practice.
Keywords: English School; pluralist vs. solidarist debate; BRICS; R2P